การพัฒนาแบบจำลองการเสื่อมสภาพผิวทางแอสฟัลต์คอนกรีตของทางหลวงในประเทศไทยด้วยกระบวนการลูกโซ่มาร์คอฟ - สิรินธร์ สืบจากรอด (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
The objective of this thesis is to develop deterioration models for asphalt concrete pavements which have average annual daily traffic more than 300 cars per day, using markov chains method. The International Roughness Index (IRI) is used to represent pavement condition. Based on data from national highways in Northern and Southeastern regions, nineteen deterioration models are developed. these models are grouped by five most influencing factors on pavement damage which resulted from the preliminary analysis. Such factors are pavement strength, surface distresses, traffic volume, construction, and environment. several conclusions can be drawn from developed models as fellows. The higher strength road would result in lower deterioration. For roads which have similar strength, traffic volume would affect deterioration rate. Furthermore, the deterioration rate of roads which have surface distresses are higher than the roads without the surface distresses. This is because surface distress would lower the strength of structural road that accelerate the deterioration of pavement. The deterioraton model can be applied for the pavement maintenance management system in order to planning for maintenance method of the roads network and planning for budget allocation.